Managing technology for translation in English class in Foreign Language students - Laura De La Cruz , Kevin Mario (2021)
This article aims to identify technological tools and how to manage them for use with students also their advantages and disadvantages for carrying out translations and interpretations. The type of research is quantitative, the procedure was worked through a virtual survey of 11 questions formulated to 143 students as a sample of the Foreign Language specialty of the Faculty of Education at the National University of Jorge Basadre Grohmann, Tacna-2020. With the results shown, the management of technological tools contributes positively to the teaching-learning process, students put into practice all the knowledge learned to achieve a neat product in translation and this way make these learnings meaningful.